Miss lazar is bizarre eaudiobook - Gutman, Dan (My Weird School, 2013)
Dan Gutman's My Weird School series tickles young listeners' funny bones with clever wordplay and zany characters. Series star A.J. is in the second grade and he hates school - but that doesn't stop him from getting into hilarious adventures. This time around, he meets a genuine superhero, school custodian Miss Lazar. Always ready to save the day, she also likes to dance around with a mop and clean up messes - she fits right in at Ella Mentry Elementary School.